Lenalidomide-based induction and maintenance in elderly newly diagnosed multiple myeloma patients: updated results of the EMN01 randomized trial - Bringhen, Sara; D'Agostino, Mattia; Paris, Laura; Ballanti, Stelvio; Pescosta, Norbert; Spada, Stefano; Pezzatti, Sara; Grasso, Mariella; Rota-Scalabrini, Delia; De Rosa, Luca; Pavone, Vincenzo; Gazzera, Giulia; et al. (Haematologica, 2020)
n the EMN01 trial, the addition of an alkylator (melphalan or cyclophosphamide) to lenalidomide-steroid induction therapy was prospectively evaluated in transplant-ineligible patients with multiple myeloma. After induction, patients were randomly assigned to maintenance treatment with lenalidomide alone or with prednisone continuously. The analysis presented here (median follow-up of 71 months) is focused on maintenance treatment and on subgroup analyses defined according to the International Myeloma Working Group Frailty Score. Of the 654 evaluable patients, 217 were in the lenalidomide-dexamethasone arm, 217 in the melphalan-prednisone-lenalidomide arm and 220 in the cyclophosphamide-prednisone-lenalidomide arm. With regards to the Frailty Score, 284 (43%) patients were fit, 205 (31%) were intermediate-fit and 165 (25%) were frail. After induction, 402 patients were eligible for maintenance therapy (lenalidomide arm, n=204; lenalidomide-prednisone arm, n=198). After a median duration of maintenance of 22.0 months, progression-free survival from the start of maintenance was 22.2 months with lenalidomide-prednisone vs 18.6 months with lenalidomide (hazard ratio 0.85, P=0.14), with no differences across frailty subgroups. The most frequent grade ≥3 toxicity was neutropenia (10% of lenalidomide-prednisone and 21% of lenalidomide patients; P=0.001). Grade ≥3 non-hematologic adverse events were rare (<15%). In fit patients, melphalan-prednisone-lenalidomide significantly prolonged progression-free survival compared to cyclophosphamide-prednisone-lenalidomide (hazard ratio 0.72, P=0.05) and lenalidomide-dexamethasone (hazard ratio 0.72, P=0.04). Likewise, a trend towards a better overall survival was noted for patients treated with melphalan-prednisone-lenalidomide or cyclophosphamide-prednisone-lenalidomide, as compared to lenalidomide-dexamethasone. No differences were observed in intermediate-fit and frail patients. This analysis showed positive outcomes of maintenance with lenalidomide-based regimens, with a good safety profile. For the first time, we showed that fit patients benefit from a full-dose triplet regimen, while intermediate-fit and frail patients benefit from gentler regimens. ClinicalTrials.gov registration number: NCT01093196.
Keywords: udržovací chemoterapie; Melphalan; prednison; výsledek terapie; přežití bez známek nemoci; doba přežití bez progrese choroby; lenalidomid; lidé; mnohočetný myelom; Lenalidomide; Prednisone; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; melfalan; Aged; dexamethason; Dexamethasone; Disease-Free Survival; Multiple Myeloma; senioři; Progression-Free Survival; Maintenance Chemotherapy; Humans